Experimental investigation on mechanical behavior of sands treated by enzyme-induced calcium carbonate precipitation with assistance of sisal-fiber nucleation - Zhang, Jianwei; Yin, Yue; Shi, Lei; Bian, Hanliang; Shi, Wanpeng (Frontiers in Earth Science, 2022)
Sisal fibers had obvious advantages of mechanical strength on reinforced enzyme-induced calcium carbonate precipitation (EICP)-cemented loose sands. However, there are few related researches, whose research on strength and toughness is not sufficient, and the analysis on mechanism is lacking. In this article, sisal fiber was used to strengthen EICP-treated sand, and the mechanical properties and underlying mechanism were experimentally explored. The results show that the strength and toughness of EICP-treated sand can be effectively improved by sisal fibers. The optimal sisal fiber length is 10 mm and the optimal fiber content is 0.2%. The wet-dry cycle resistance of the samples is improved simultaneously. Microscopic study showed that the rough surface of sisal fiber provided a large number of nucleation sites for calcium carbonate precipitation and formed an effective “bridge network.” This study reports the potential and the underlying mechanism of sisal fiber on improvement of EICP performance by new test methods and provides new insight into enhancing mechanical behavior of EICP-cemented loose sands with natural fiber.